Kedudukan Hukum Peminangan Dalam Perkawinan Perspektif Hukum Adat Dan Hukum Islam - Khailid, Muhammad; Tanjung, Dhiauddin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
This research is motivated by the large number of prospective married couples who do not carry out the ta'aruf process in khitbah in accordance with Islamic teachings. In the practice of khitbah, there are still customary rules which make it difficult, resulting in the prevention of marriage. The purpose of this research is to dig up information on how the concept of Khitbah in the concept of Malay custom, its correlation and relationship with Islamic teachings. The method used in this research is field research by observing and interviewing, and studying books related to this discussion. The primary source is in the form of books by scholars' which are related to the concept of Khitbah. Ta'aruf and khitbah in Shari'a recommend prioritizing religious aspects over other factors. Because only religion will be able to perpetuate marriage. While wealth, lineage, position, beauty, good looks will fade and one day will disappear and avoid khalwat elements in it